Equipamentos de proteção individual: o olhar dos trabalhadores de enfermagem em um hospital universitário - NEVES, Heliny Carneiro Cunha (2009)
The recommendations from the standard precautions that included the concepts of universal precautions have been applied for more than 15 years. This primary prevention of occupational exposure remains efficient and effective in protecting professional health care (PHC). However, we found that adherence to these measures is sometimes discontinuous and contradictory and leads to an enhancement of the risks and substantial increase in exposure to biological material. This leads us to inquire about other factors that may contribute to this kind of behavior on the part of PHC. From this perspective, investigating the subjective aspects that influence the behaviors and attitudes of nursing professionals to join the personal protective equipment (PPE) becomes important. The objective of this study was to analyze the reasons, attitudes and beliefs of nursing staff regarding adherence to PPE. Qualitative study conducted in December 2008 in a large university hospital in the city of Goiania. We observed the ethical-legal aspects. Data were collected through focus group technique using guiding questions. The study included 15 professionals of nursing, which formed three focus groups with five participants in each group. Data were analyzed by the model of health beliefs (MCS) of Rosenstock (1974b) and the method of interpretation of meaning, according to security issues at work and Interpersonal Relationship. We could identify that interpersonal relationships interfere with issues of safety and personal protection at various levels in the workplace, both in the organizational and manage, and in relation to other professions and other sectors of the hospital. This relationship proved is a two-way process and we cannot ignore the factors and individual risk perception, which is connected with the work environment, influence the individual protection. Difficulties such as work overload, stress, lack of motivation, communication, and inadequate physical infrastructure, lack of availability and limited access to PPE, lack of routines and the assistance process after exposure to biological material, among others, interfere with adherence to such safety equipment, but not determine them. Joining the PPE is impregnated by the context as experienced in the workplace, but also by individual values and beliefs, but the decision to use the PPE is personal. The numbers of perceived barriers in the work environment are opposing forces that cancel the driving forces for adherence to personal protective equipment. We note that the qualitative and focus group technique provided us with input for analysis and reflection on the accession to the PPE as well as direct possible strategies and effective measures to prevent and control infections and improve adherence to safety equipment.